HUBUNGAN PENGETAHUAN DAN KARAKTERISTIK IBU BADUTA DENGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KELURAHAN MERUYA UTARA TAHUN 2020 - Septia Nur Rahma (2021)
The giving of exclusive breastfeed is the giving of only breast milk to infant without other liquids or solids are given except vitamins and medicines if needed. Based on data released by WHO, there are only 38% of babies aged 0 to 6 months in worldwide who receive exclusive breastfeed. The number of factors that can influence mothers in exclusively breastfeeding are sociodemographic factors including mother's age, education, knowledge, and job. This research was conducted on mothers who have children aged 6-24 months in the North Meruya Village area on August 2020 until January 2021. The purpose of this research was to analyze the relationship of mother's knowledge and characteristics with the giving of exclusive breastfeed in the area of Meruya Utara Village. This study used Cross Sectional design study with 194 samples. The statistical test used is the Chi-Square test with a significance level of 0.05. Based on the results of this research showed that 46.9% mothers had given an exclusive breastfeed. The results of the bivariate analysis showed that there was significant relationship between mother's knowledge (p-value = 0.030), mother's age (p-value = 0.022), and mother's education level (p-value = 0.017) with the giving of exclusive breastfeed. Meanwhile, the variables that did not have a significant relationship were job status (p-value = 0.250) and income level (p-value = 0.673). Mothers who have children aged 6-24 months are advised to routinely access health information independently via internet to obtain information related to Maternal and Child Health. Health officers and village health worker in the area of North Meruya Village can provide more intense information and education to mothers or expectant mothers to carry out exclusive breastfeeding as a promotional effort to improve community health status.